JWST Near-infrared Spectroscopy of the Lucy Jupiter Trojan Flyby Targets: Evidence for OH Absorption, Aliphatic Organics, and CO2 - Ian Wong; Michael E. Brown; Joshua P. Emery; Richard P. Binzel; William M. Grundy; Simone Marchi; Audrey C. Martin; Keith S. Noll; Jessica M. Sunshine (The Planetary Science Journal, 2024)
We present observations obtained with the Near Infrared Spectrograph on JWST of the five Jupiter Trojans that will be visited by the Lucy spacecraft—the Patroclus–Menoetius binary, Eurybates, Orus, Leucus, and Polymele. The measured 1.7–5.3 μ m reflectance spectra, which provide increased wavelength coverage, spatial resolution, and signal-to-noise ratio over previous ground-based spectroscopy, reveal several distinct absorption features. We detect a broad OH band centered at 3 μ m that is most prominent on the less-red objects Eurybates, Patroclus–Menoetius, and Polymele. An additional absorption feature at 3.3–3.6 μ m, indicative of aliphatic organics, is systematically deeper on the red objects Orus and Leucus. The collisional fragment Eurybates is unique in displaying an absorption band at 4.25 μ m that we attribute to bound or trapped CO _2 . Comparisons with other solar system small bodies reveal broad similarities in the 2.7–3.6 μ m bands with analogous features on Centaurs, Kuiper Belt objects (KBOs), and the active asteroid 238P. In the context of recent solar system evolution models, which posit that the Trojans initially formed in the outer solar system, the significant attenuation of the 2.7–3.6 μ m absorption features on Trojans relative to KBOs may be the result of secondary thermal processing of the Trojans’ surfaces at the higher temperatures of the Jupiter region. The CO _2 band manifested on the surface of Eurybates suggests that CO _2 may be a major constituent in the bulk composition of Trojans, but resides in the subsurface or deeper interior and is largely obscured by refractory material that formed from the thermophysical processes that were activated during their inward migration.